1971
DOI: 10.1002/bjs.1800580115
|View full text |Cite
|
Sign up to set email alerts
|

“Spontaneous” perforation of the oesophagus treated by utilization of a pericardial flap

Abstract: SUMMARYA case of 'recurrent' spontaneous perforation of the oesophagus treated by the utilization of a pericardial flap is reported. It is suggested that this manaeuvre, which does not appear to have been described previously, may be life-saving when there has been delay in operating or major secondary leakage has occurred. THE purpose of this report is to record the successful management of a case of spontaneous perforation of the oesophagus using a flap of pericardium to reinforce the repair after there had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1972
1972
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Reinforcement of the primary repair has been advocated by many surgeons. [15][16][17] We favor use of a pleural flap for middle third injuries and the omental flap for lower third ruptures. Primary repair is not advisable in some situations, such as: underlying malignant disease, scleroderma, grade IV reflux esophagitis and stage III achalasia.…”
Section: Discussionmentioning
confidence: 99%
“…Reinforcement of the primary repair has been advocated by many surgeons. [15][16][17] We favor use of a pleural flap for middle third injuries and the omental flap for lower third ruptures. Primary repair is not advisable in some situations, such as: underlying malignant disease, scleroderma, grade IV reflux esophagitis and stage III achalasia.…”
Section: Discussionmentioning
confidence: 99%
“…Also, because of the high incidence of anastomotic insufficiency, tissues such as the omentum, base of the stomach, pericardium, or pleura have been used to cover the perforation site in recent years [14][15][16], although some studies have found that T-tube insertion is effective for severe contamination in the ruptured area [11,17].…”
Section: Discussionmentioning
confidence: 99%
“…The oesophagus can also perforate into the pericardium (Shackelford, 1931), though more commonly it perforates into the chest. Spontaneous perforation of the oesophagus into the pleural cavity was first successfully treated by operation by Barrett (I 948), and a recent suggestion to help in the technique of repair is the use of a flap of pericardium (Millard, 1971). However, the development of a fistula into the pericardium is much rarer and more sinister.…”
Section: Discussionmentioning
confidence: 99%